การฉีดขึ้นรูปผงอะลูมินาและวัสดุเชิงประกอบอะลูมินา / ทังสเตนคาร์ไบด์ - จุฑาเทพ สุรวัฒนา (จุฬาลงกรณ์มหาวิทยาลัย, 2011)
This study focuses on alumina and alumina/tungsten carbide composites fabricated by powder injection moulding using a PEG/PVB co-binder. The starting powders are alumina and alumina/tungsten carbide. The alumina/tungsten carbide composites with the ratio of Al₂O₃ to WC of 90:10 wt%, were also prepared. The binder, consists of polyethylene glycol (PEG) and polyvinyl butyral (PVB). The ratios of PEG:PVB were ranged from 80:20, 85:15 and 90:10 wt% whereas stearic acid (SA) was used as an additive. Both powders and binders were mixed thoroughly and the powder loadings were varied from 44 to 52 vol%. The injection moulded temperatures were ranged from 190 to 210 ºC, depending on the feedstock makeup. Double debinding steps were carried out using water leaching at 30, 45 and 60 ºC to remove PEG and thermal debinding at 400 ºC for PVB removal. Then, the specimens were sintered at 1600 ºC for 2 hours in argon. Characteristics of the as-injected, the as-leached and the as-sintered including density, apparent porosity, flexural strength, hardness as well as microstructure were determined. The results revealed that these co-binders offered dimensional stability. PEG removal depended on water temperatures and more than 95% of PEG binder could be easily removed within 5 hours. A small amount of the remained PVB could sustain the shapes. Flexural strength, hardness and density after sintering of both alumina and alumina/tungsten carbide directly involved with powder loadings. The present work suggested that alumina and alumina/tungsten carbide particulate composites can be fabricated by powder injection moulding using a water soluble co-binder. This technique is possible to be applied in industrial practice.